Hemp Reinforced Composites with Alkalization and Acetylation Fibre Treatments. Issue 3 (March 2014) - Wang, H.; Kabir, M.M.; Lau, K.T.
The increasing ecological and environmental concerns have led to the development of natural fibre composites. Chemical treatments are usually used to modify the surface of fibre to improve the bonding between fibre and resin. Alkalization and acetylation were used in this study to treat the hemp fibre. It was found that the chemical treatments remove the impurity and lignin, increasing the cellulose content of the hemp fibre. Removal of the surface lignin and hemicelluloses also exposes more active hydroxyl groups from cellulose to react with matrix. All theses lead to the increase of mechanical properties. It is also noticed that excessive treatment is detrimental to the fibre internal structure itself and weaken the fibre.